Common breastfeeding problems. Issue 7 (July 2020) - Anipindi, Shailaja; Field, Alexander; Neville, Corinne; Field, Elizabeth
The health benefits of breastfeeding are well known; the majority of women in the UK express a desire to breastfeed. However, by 8 weeks of age, only 40% of babies are receiving any breastmilk. Many reasons are given for discontinuing, but GPs, as a primary contact for women concerned about breastfeeding, are often able to identify problems. The aim of this article is to explore what constitutes successful breastfeeding, common concerns expressed by mothers, the pathologies with which they present to GPs and how breastfeeding fits into a holistic picture of postnatal health.